2011
DOI: 10.1016/j.otsr.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The arthritic wrist. II - The degenerative wrist: Indications for different surgical treatments

Abstract: For the patient (and the surgeon) the ideal wrist is one that has good mobility, however very often the optimal surgical treatment is one that provides effective pain relief. The patient must be informed of the potential complications and limitations of each procedure. The patient's psychological profile and functional requirements will determine how well he/she adapts to the changes. Also, each surgeon has beliefs and personal experiences that influence the treatment decision and final result. Proximal row ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 23 publications
0
19
1
2
Order By: Relevance
“…Despite limited follow-up, the results of our series show that Amandys 1 arthroplasty is a valid alternative to the more conventional invasive procedures such as total wrist arthrodesis and arthroplasty using a total or partial prosthesis. The preservation of wrist mobility is actually the most important functional priority for patients along with pain relief [5,40]. These objectives are attained in our series.…”
Section: Preoperative (Sd)mentioning
confidence: 86%
“…Despite limited follow-up, the results of our series show that Amandys 1 arthroplasty is a valid alternative to the more conventional invasive procedures such as total wrist arthrodesis and arthroplasty using a total or partial prosthesis. The preservation of wrist mobility is actually the most important functional priority for patients along with pain relief [5,40]. These objectives are attained in our series.…”
Section: Preoperative (Sd)mentioning
confidence: 86%
“…3,9,16 Despite clinical studies reporting adequate outcomes regarding postoperative range of motion and grip strength, 10 Kirschenbaum et al 8 reported a nonunion incidence rate of 33%. However, their results were likely attributed to the precarious nature of the osteosynthesis material (pins).…”
Section: Discussionmentioning
confidence: 99%
“…Scans were collected of each specimen in neutral, flexion, extension, radial, and ulnar deviation before and after each surgical procedure was performed ( [1] scaphoidectomy and lunate-capitate arthrodesis, [2] addition of triquetrum-hamate arthrodesis, and [3] triquetrum excision). CT scans were reconstructed in both coronal and sagittal planes.…”
Section: Imaging Evaluationmentioning
confidence: 99%
See 2 more Smart Citations